GGR 2020
DOI: 10.31487/j.ggr.2020.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Skills Questionnaire: Comparative Results in Elderly Population without Cognitive Deficit, Mild Cognitive Impairment and Alzheimer's Disease

Abstract: The increase in consultations for changes and/or cognitive complaints in the elderly, together with the current interest in epidemiological research in this context creates the need for screening tools for cognitive assessment to enable the detection of early deficits. Evidence shows its predictive value in the development of dementia disease. This study aims at displaying the results of a Cognitive Skills Questionnaire (CSQ) in a patient population with mild cognitive impairment (MCI) and Alzheimer’s disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…The negative impact on both mental and physical health has also been reported in Latin America, including Argentina. For example, lockdown periods have been associated with increased levels of psychological distress, fear of COVID-19, sleep problems, and reduced mood in both children [7][8][9][10][11] and the general adult population [12][13][14][15][16][17][18][19][20]. In addition, studies in Latin America revealed that lockdowns are associated with an increase in a number of unhealthy behaviors, such as poorer daily diet [21], weight gain [22], poorer sleep quality [14,19], and reduced physical activity [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact on both mental and physical health has also been reported in Latin America, including Argentina. For example, lockdown periods have been associated with increased levels of psychological distress, fear of COVID-19, sleep problems, and reduced mood in both children [7][8][9][10][11] and the general adult population [12][13][14][15][16][17][18][19][20]. In addition, studies in Latin America revealed that lockdowns are associated with an increase in a number of unhealthy behaviors, such as poorer daily diet [21], weight gain [22], poorer sleep quality [14,19], and reduced physical activity [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Se realizó una entrevista inicial individual en la cual se tomaron los test de ACE III y Estudio de Funcionalidad Compleja (Labos et al, 2018). Se realizó una adaptación de este último, tomando solo los puntajes secundarios del test ya que estos mismos permitían recabar datos sobre el desempeño actual en el uso de las TICs de las personas participantes.…”
Section: Diseño Y Muestraunclassified